Interplay of TRIM2 E3 Ubiquitin Ligase and ALIX/ESCRT Complex: Control of Developmental Plasticity During Early Neurogenesis - Ashwin Lokapally; Herbert Neuhaus; Juliane Herfurth; Thomas Hollemann (Cells, 2020)
Tripartite motif 2 (TRIM2) drives neurite outgrowth and polarization, is involved in axon specification, and confers neuroprotective functions during rapid ischemia. The mechanisms controlling neuronal cell fate determination and differentiation are fundamental for neural development. Here, we show that in Xenopus, trim2 knockdown affects primary neurogenesis and neural progenitor cell survival. Embryos also suffer from severe craniofacial malformation, a reduction in brain volume, and the loss of motor sensory function. Using a high-throughput LC-MS/MS approach with GST-Trim2 as bait, we pulled down ALG-2 interacting protein X (Alix) from Xenopus embryonic lysates. We demonstrate that the expression of trim2/TRIM2 and alix/ALIX overlap during larval development and on a cellular level in cell culture. Interestingly, trim2 morphants showed a clustering and apoptosis of neural progenitors, which are phenotypic hallmarks that are also observed in Alix KO mice. Therefore, we propose that the interaction of Alix and Trim2 plays a key role in the determination and differentiation of neural progenitors via the modulation of cell proliferation/apoptosis during neurogenesis.